Implementación del teatro infantil como instrumento pedagógico para la recreación de los niños de 4-5 años del jardín “semillitas” del cantón pujilí en el periodo académico 2010-2011” - Latacunga Pilatásig, María Rebeca (2013)
The investigation refers to the implementation of a theater as a pedagogical tool for children‘s entertainment knowing that theater schools, by means of games and group or individual activities, are ideal to help children develop verbal and body expression, and to stimulate children‘s capacities and mental agility. The present investigation deals with the way of carrying out a theater with the students, which is based on infantile dramatization, with which, first grade of basic education children will be able to develop their capacities using strategies that encourage them with fictional and real-life characters. The investigation was carried out for the need of implementing infantile theater because it was not implemented previously; and for that reason based on the poll done to teachers and parents, concrete conclusions are reached which are a mean to awaken interest in the boys and girls, and at the same time they can be able to perform fluently portraying characters that transmit feelings and values. The investigation ends with the presentation of theatrical works which the teacher will apply when it could be convenient in or outside the classroom.